An application of non-linear co-integration test model to gold inflation hedging ability - Ho, Tran Thao Nguyen (Trường Đại học Kinh tế, 2020)
This study aims to analyze the question of how effective gold is as an inflation hedge in both long-term and short-term in Vietnam from a new perspective – non-linear co-integration. The two-stage testing procedure is applied to analyze the inflation hedging ability of gold in Vietnam both in long and short-run with monthly data of gold price from World Gold Council (per ounce denominated in Vietnam Dong) and CPI of Vietnam from International Monetary Fund (IMF) over the period of January 1995 to July 2014 are used for analysis. The results figure out the long-term effective hedging ability but unstable relationship between gold and inflation. To further explore the inflation hedging ability of Gold in short-run, the study uses the non-linear error-correction model (TC-TVECM) to examine the price rigidity in low regime (when variation margin of gold price is lower than that of CPI) and high regime (when variation margin of gold price is higher). It is found that in short-run, gold is partially effective in hedging against inflation. The protection ability is stronger in low momentum than in high momentum. Furthermore, by comparing the results in two countries – Vietnam and Thailand, this research tries to provide a broader view on inflation-hedge of gold across South-east Asian countries